2014
DOI: 10.5812/numonthly.20748
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease Progression in Elderly Iranian Patients: a Cohort Study

Abstract: Background:In the past few decades, Chronic Kidney Disease (CKD) - a disease with progressive decline in renal function - has become an important problem of global public health, not only in developed countries, but also in developing countries with less economic power.Objectives:In this study, CKD progression to death or End Stage Renal Disease (ESRD) in elderly Iranian patients was compared with younger counterparts.Patients and Methods:This retrospective cohort study was conducted on CKD patients with estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…In a 3.322 adults patients cohort, 13% of the patients that declined kidney function 77% were elderly [8]. However, like ours, other studies [8, 13, 17] showed that the eGFR slope and its magnitude were higher in younger patients. A possible explanation for that, suggested by O´Hare et al, [18] is the competing risk for death over end renal stage kidney disease present in the elderly population.…”
Section: Discussionsupporting
confidence: 45%
“…In a 3.322 adults patients cohort, 13% of the patients that declined kidney function 77% were elderly [8]. However, like ours, other studies [8, 13, 17] showed that the eGFR slope and its magnitude were higher in younger patients. A possible explanation for that, suggested by O´Hare et al, [18] is the competing risk for death over end renal stage kidney disease present in the elderly population.…”
Section: Discussionsupporting
confidence: 45%
“…Aunque la relación de la edad avanzada con la aparición y la mayor progresión de la ERC se ha encontrado de manera sistemática en otros estudios [16,17], otros reportes, al igual que este, han mostrado que la pérdida de TFG es mayor en los pacientes más jóvenes [18,19]. O'Hare et al [20] han aportado una posible explicación para este hallazgo y es el riesgo competitivo de la muerte sobre la llegada a enfermedad renal terminal presente en la población mayor.…”
Section: Discussionunclassified
“…According to the report provided by the National Organization for Civil Registration of Iran, 2,243,249 individuals were referred to all health-care centers in Isfahan from 2017 to 2019. The sample size of this study included 3374 individuals that were selected from the mentioned population at 95% confidence interval, the test power of 80%, and considering the prevalence of CKD reported in recent studies[ 4 ] conducted in our country equal to 6%, and the error level of 0.008.…”
Section: Methodsmentioning
confidence: 99%
“…Considering that the progression of CKD can be prevented by controlling some modifiable risk factors such as blood pressure, cardiovascular events, blood sugar, nephrotoxic drugs, obesity, and salt intake,[ 4 5 6 ] it seems essential to pay due attention to the potential risk factors in this regard to prevent the development of CKD. In this regard, excessive or prolonged alcohol consumption as one of the most common psychedelics in the world is considered a potential risk factor for cardiovascular diseases such as hypertension (HTN) and cerebrovascular accidents.…”
Section: Introductionmentioning
confidence: 99%